(untitled) (Scientific journal of the Fergana State University, 2022)
The influence of the composition of the solvent in the process of dewaxing oils: toluene, benzene, methyl ethyl ketone, acetone, C2-C5 alcohols was studied, and it was determined that in the process of dewaxing oils, the loss of acetone reaches 55 ± 5%, the freezing point of the oil decreased to minus 50°C, increasing the oil separation to 6%. The amount of oil in the slack decreases to 8%, the fraction (100-125)°C of the obtained toluene concentrate, together with the alcohol fraction (C2-C5), accelerates the dewaxing of the oil.